CHARACTER EDUCATION BASE ON QUR’AN ON EARLY CHILDREN IN THE DIGITALIZATION ERA - Annisa, Anni; Yudiati, Rini (Proceeding International Seminar of Islamic Studies, 2023)
Technology is widely used in the world of education, as a means and infrastructure for interaction between educators and students. Current technological developments have positive and negative impacts, preferably positive impacts are more dominantly utilized by technology users. Today's children integrate a lot with technology, such as gadgets and video games. Now, children spend more time with the media every day, if the child's interaction with technology without getting the guidance of teachers and parents will damage the child's character. In fact, failure to cultivate character from an early age will form a problematic person in his adulthood. Quality character needs to be formed and nurtured from an early age. Early age is a critical period for the formation of one's character. The research objective to be achieved is to describe the efforts of Al-Hasan PAUD teachers in shaping the character of students in the digitalization era through Al-Qur'an-based methods. The research method used is descriptive qualitative method. The subjects in this study were Al-Hasan PAUD teachers and students. Methods of data collection using the method of observation, interviews, and documentation. The data analysis technique uses interactive analysis with data reduction, data presentation, and conclusion drawing steps. The results of the study show that the efforts of Al-Hasan PAUD teachers in building character through the Al-Qur'an based method.